Perjanjian Secara Online Dalam Fitur Paylater Berdasarkan Hukum Perjanjian. - Putri Sari Perdani; Christina Tabita Sitanggang; Sumriyah Sumriyah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The increasing public interest in using the paylater feature on the Shopee application is still increasing and quite a few people do not understand their rights and obligations in using this feature. In order to provide certainty and protection for users and business actors, regulations are needed for paylater service providers. This research was created to analyze the form of agreement that arises in the implementation of sales and purchases using the Shopee Paylater feature, including the legal relationship between the parties to the transaction. The panel research method used is normative juridical which examines only library data or secondary data, which includes primary, secondary and tertiary legal materials. According to existing research results, the agreements that occur in Shopee Paylater transactions with users based on the analysis of Article 1313 of the Civil Code do not conflict and this agreement is valid as explained in Article 1320 of the Civil Code. This agreement can occur in transactions which are standard agreements, namely agreements where the existing terms and conditions have been regulated unilaterally by the agreement provider. The standard agreement contained in the agreement in this paylater feature is regulated in Article 1319 of the Civil Code. The legal relationship between the parties concerned is PT. Commerce Finance as a creditor with Shopee Paylater consumers as a debtor based on a loan agreement as stated in Article 1754 of the Civil Code. The legal relationship that exists between PT. Commerce Finance with PT. LDN which is the giver of power of attorney and recipient of power of attorney. This of course makes PT. LDN has the right to distribute funds to the relevant Shopee Paylater users.